Brain targeting stealth lipomers of combined antiepileptic-anti-inflammatory drugs as alternative therapy for conventional anti-Parkinson's - Iman M. Higazy (Elsevier, 2020)
This study presents an alternative therapy to conventional anti-Parkinson's treatment strategies; where motor and non-motor symptomatic complications are considered. Thus; providing sustainability, patient compliance, therapeutic safety and efficiency, based on triggering secretion of endogenous dopamine (DA). Exogenous DA has long been considered the best therapy, however, its poor blood brain barrier (BBB) permeability, fluctuated plasma levels, and non-motor complications negligence, decreased response to therapy with time. Consequently; brain targeting Tween®80-coated pegylated lipomers were tailored for intravenous administration (IV) of L-Dopa, and two drugs of reported neuroprotective effect: lamotrigine (LTG) and tenoxicam (TX). Single-step nanoprecipitation method was used; for its reproducibility and ease of scaling-up. Formulation targeting and anti-PD efficiency was evaluated against marketed standards and L-Dopa. In-vitro and in-vivo pharmacokinetic and dynamic studies were carried out for setting optimization standards upon varying inter-components ratio. Results revealed that lipomers are, generally, significantly efficient in brain targeting compared to oral tablets. LTG-lipomers (LF20) showed the maximum anti-PD compared to its TX and L-Dopa analogues. Combining LTG and TX had synergistic effect; highlighting a new prescription for both drugs. Thus; offering a safe, targeted, and therapeutically efficient sustained dosage form, capable of mitigating PD risk and treating it though weekly administration. Hence; presenting a novel promising anti-neurodegenerative strategy; on employing various mechanisms that were previously achieved through additional therapeutic supplements. Keywords: Neurodegeneration, Antiepileptics, Anti-inflammatory, Pegylated, Lipomers, Brain targeting